Exploring methane cycling in an arctic lake in Kangerlussuaq Greenland using stable isotopes and 16S rRNA gene sequencing - Cadieux, Sarah B.; Schütte, Ursel M. E.; Hemmerich, Chris; Powers, Sarah; White, Jeffrey R. (Frontiers in Environmental Science, 2022)
Lakes are currently responsible for a significant amount of total natural methane emission. Microbial oxidation of methane plays a central role in Arctic carbon cycling, potentially reducing methane emissions from lakes, though little is known about methane cycling in the water column of Arctic lakes. We previously detected surprisingly large enrichments of carbon and hydrogen isotopes of methane in three small lakes in Greenland suggesting unusually efficient methanotrophic communities in these Arctic lakes. Using stable isotope and 16S rRNA gene sequencing we determined carbon and hydrogen isotopes and microbial community composition down the water column of Teardrop lake, under open-water conditions. We found that isotopic values of methane in Teardrop lake were again highly enriched at 4 m depth with -13.2 ‰ and -27.1 ‰ values for carbon and hydrogen isotopes, respectively. Surprisingly, methane concentrations slightly increased at the interval with isotope enrichment, not typical of classic methanotrophy. Consistent with isotopic enrichment we detected the highest relative abundance of putative methanotrophs, in particular Methylovulum at 4 m. The highest relative abundance of putative methanogens was detected at 3 m as well as at 5 m. At the same depth interval, temperature and oxidation reduction potential also increase, supporting increased microbial activity mid-depth. Based on geochemical and microbial observations, we suggest that the methane cycling in Teardrop lake is decoupled from a traditional depth dependent model where the dominant source of methane is in the anoxic sediments. Instead, methane in the water column is likely from a combination of anoxic sediment, littoral transport and oxic methanogenesis in the mid-water column, and recycling of carbon within the water column is leading to extreme isotope enrichments. Thus, understanding linkages between depth-dependent microbial dynamics and methane biogeochemistry are necessary to constrain the sensitivity of the methane cycle to future climate change.